Therapeutic Efficacy of Human Mesenchymal Stem Cells With Different Delivery Route and Dosages in Rat Models of Spinal Cord Injury. (November 2022) - Liu, Guangyang; Zhao, Zhiling; Wang, Herui; Hao, Chunhua; Wang, Weiting; Zhang, Chenliang; Wang, Tiehua; Li, Xin; Xi, Jingjing; Li, Shaoyun; Long, Haomiao; Mi, Yi; et al.
Recent studies have shown that the use of mesenchymal stem/stromal cells (MSCs) may be a promising strategy for treating spinal cord injury (SCI). This study aimed to explore the effectiveness of human umbilical cord-derived MSCs (hUC-MSCs) with different administration routes and dosages on SCI rats. Following T10-spinal cord contusion in Sprague-Dawley rats (N = 60), three different dosages of hUC-MSCs were intrathecally injected into rats (SCI-ITH) after 24 h. Intravenous injection of hUC-MSCs (SCI-i.v.) and methylprednisolone reagent (SCI-PC) were used as positive controls (N = 10/group). A SCI control group without treatment and a sham operation group were injected with Multiple Electrolyte Injection solution. The locomotor function was assessed by Basso Beattie Bresnahan (BBB) rating score, magnetic resonance imaging (MRI), histopathology, and immunofluorescence. ELISA was conducted to further analyze the nerve injury and inflammation in the rat SCI model. Following SCI, BBB scores were significantly lower in the SCI groups compared with the sham operation group, but all the treated groups showed the recovery of hind-limb motor function, and rats receiving the high-dose intrathecal injection of hUC-MSCs (SCI-ITH-H) showed improved outcomes compared with rats in hUC-MSCs i.v. and positive control groups. Magnetic resonance imaging revealed significant edema and spinal cord lesion in the SCI groups, and significant recovery was observed in the medium and high-dose hUC-MSCs ITH groups. Histopathological staining showed that the necrotic area in spinal cord tissue was significantly reduced in the hUC-MSCs ITH-H group, and the immunofluorescence staining confirmed the neuroprotection effect of hUC-MSCs infused on SCI rats. The increase of inflammatory cytokines was repressed in hUC-MSCs ITH-H group. Our results confirmed that hUC-MSC administered via intrathecal injection has dose-dependent neuroprotection effect in SCI rats.